2012
DOI: 10.1071/ch11292
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peptide Core Nanoparticles as Multivalent Vaccine Candidates against Streptococcus pyogenes

Abstract: Traditional vaccine approaches for Group A streptococcus (GAS) infection are inadequate owing to the host’s production of cross-reactive antibodies that recognize not only the bacteria but also human tissue. To overcome this problem a peptide subunit-based vaccine was proposed, which would incorporate only minimal non-cross reactive epitopes. However, special delivery systems/adjuvants were required because short peptides are not immunogenic. In this study we have incorporated two epitopes from two different G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…21,[39][40][41] Analysis of the reaction showed that instead of the desired 'click' product 3, a disulfide bond-mediated dimer of 2 was exclusively produced.…”
Section: Resultsmentioning
confidence: 99%
“…21,[39][40][41] Analysis of the reaction showed that instead of the desired 'click' product 3, a disulfide bond-mediated dimer of 2 was exclusively produced.…”
Section: Resultsmentioning
confidence: 99%
“…The conjugation was performed as previously described [27,28]. Briefly, compounds 3 (2.05 mg, 1.65 x 10 -3 mmol) and 7 (7.41 mg, 1.65 x 10 -3 mmol) were dissolved in DMF (1 mL) and copper wires were added (70 mg).…”
Section: Conjugate (9) Of Compounds 3 Andmentioning
confidence: 99%
“…The synthesis was performed in a similar manner to that previously reported. 15,19,48 Briefly, Boc-deprotection was performed with neat TFA (2 × 1 min), followed by a 1 min DMF flow wash. Boc-protected amino acids (4.2 equiv.) were pre-activated with 0.5 M HBTU/DMF solution (4.0 equiv.…”
Section: Synthesis Of Peptide Epitopes and Lcpsmentioning
confidence: 99%